Creencias conspirativas y religiosidad relacionados con el miedo a la COVID-19 en estudiantes universitarios de Lima Metropolitana - Huerta Rosales, Rosa Elena (2025)
This study analyzes the association between religiosity and conspiracy beliefs with fear of COVID-19 in a sample of 661 university students, of both sexes, from public and private universities in Lima, Peru. Sociodemographic data were collected, along with the Fear of COVID-19 Scale (Ahorsu, 2020), the Religiosity Scale (Gorsuch & Venable, 1983), and the General Conspiracist Beliefs Scale (Rezende et al., 2021). Results showed that women reported higher levels of fear of COVID-19 but lower levels of intrinsic religiosity, personal extrinsic religiosity, and social extrinsic religiosity, although the magnitude of these differences was small. Furthermore, participants with higher levels of fear of COVID-19 tended to show stronger beliefs in extraterrestrial cover-up conspiracies and lower levels of all dimensions of religiosity. At the multivariate level, according to logistic regression, social extrinsic religiosity and conspiracy beliefs related to global conspiracies, extraterrestrial cover-ups, and information control were significant predictors of high levels of fear of COVID-19. Among these, social extrinsic religiosity was the strongest predictor, increasing the likelihood of elevated fear.